Incidence of inbreeding and its influence on performance traits in Sahiwal cattle - Shabahat Mumtaz,; Anupama Mukherjee, (Journal of Livestock Biodiversity, 2025)
Pedigree and performance records of 1712 Sahiwal female maintained at ICAR-National Dairy Research Institute, Karnal pertaining to the period between1974 to 2018 were utilized for present study. Present investigation was carried out to find out the influence of inbreeding on various performance traits in female population. Data is adjusted for non-genetic factors namely season/period of birth for age at first calving and season/period of calving for first service period, first calving interval, first lactation 305 days or less milk yield, first lactation length, first lactation total milk yield, first dry period, first lactation 305 fat yield and first lactation 305 solid not fat yield the data pertaining to first lactation traits considered. The data was classified into 5 inbreeding groups including non-inbred group to study the influence of inbreeding on above traits by taking inbreeding as a fixed effect by using least square analysis of variance. The inbreeding coefficient of Sahiwal female population was 2.21% and inbred female was 3.7% ranging from 0.01 to 20%. Most of the traits were non-significant only age at first calving were statistically significant (P≤0.01) among various inbred groups. The main reason of low level of inbreeding firstly was implementation of optimum breeding strategies that leads to introduction of new genetics variants and culling of animals to avoid mating of related ones in the herd and secondly due to incompleteness of pedigree especially for animals born in earlier years with unknown pedigree mainly founders. Although there was no inbreeding depression in most of the traits but inbreeding effect were showing slightly increasing trend on service period and calving interval so more precise pedigree recording and planned mating strategies should be adopted to avoid inbreeding depression in future generation.